The noncoding RNA AK127244 in 2p16.3 locus: A new susceptibility region for neuropsychiatric disorders. Issue 6 (14th August 2018) - Rizzo, Ambra; Alfei, Enrico; Zibordi, Federica; Saletti, Veronica; Zorzi, Giovanna; Freri, Elena; Estienne, Margherita; Girgenti, Vita; D'Arrigo, Stefano; Esposito, Silvia; Buldrini, Barbara; Moroni, Isabella; et al.
Abstract : The presence of redundant copy number variants (CNVs) in groups of patients with neurological diseases suggests that these variants could have pathogenic effect. We have collected array comparative genomic hybridization (CGH) data of about 2, 500 patients affected by neurocognitive disorders and we observed that CNVs in 2p16.3 locus were as frequent as those in 15q11.2, being both the most frequent unbalances in our cohort of patients. Focusing to 2p16.3 region, unbalances involving NRXN1 coding region have been already associated with neuropsychiatric disorders, although with incomplete penetrance, but little is known about CNVs located proximal to the gene, in the long noncoding RNA AK127244. We found that, in our cohort of patients with neuropsychiatric disorders, the frequency of CNVs involving AK127244 was comparable to that of NRXN1 gene. Patients carrying 2p16.3 unbalances shared some common clinical characteristics regardless NRXN1 and AK127244 CNVs localization, suggesting that the AK127244 long noncoding RNA could be involved in neurocognitive disease with the same effect of NRXN1 unbalances. AK127244 as well as NRXN1 unbalances seem to have a particular influence on language development, behavior or mood, according with the topographic correlation between NRXN1 expression and prefrontal cortex functions.